Criterion validity of metabolic and anthropometric predictors in diabetic foot syndrome - Bubanja, Dragana; Jovanović, Zorica; Vuković, Mira (Vojnosanitetski pregled, 2021)
Background/Aim. The diabetic foot syndrome (DFS) appears in 15% of diabetes mellitus (DM) patients and is the most common cause of hospitalization, prolonged hospital stay and lower extremity amputation. This study assesses the discriminant validity of the indicators of glycemic control, lipoprotein status and the body mass index (BMI) in diagnosing DFS in the DM patients. Methods. A comparative observational study was conducted with the study group composed of patients diagnosed with DM and DFS and a control group, composed of healthy volunteers. Metabolic predictors measured in the study were: fasting glycaemia (FG), postprandial glycaemia (PPG), glycated hemoglobin (HbA1c), total cholesterol, total triglyceride, low density lipoprotein (LDLc) and high density lipoprotein (HDLc). The BMI was measured as an anthropometric variable. The validity criterion of both metabolic and anthropometric variables was estimated by the Receiver Operating Characteristic (ROC) procedure. Results. A total of 70 patients with DM and 60 healthy volunteers were observed. Using the ROC procedure, five significant predictors of DFS were proved. The validity criterion for HbA1c, FG, PPG, LDLc and the BMI were in the following order: 6.3%, 6.3 mmol/L, 7.1 mmol/L, 4.39 mmol/L and 25 kg/m2, respectively. Significantly larger surfaces were found under the curve for all glycometabolic variables, compared to the surface under the curve for LDLc, as well as relative to the surface under the curve for BMI. Conclusion. Preventing DFS in patients with DM has to include intensification of diet measures along with the treatment of the increased value of fasting glycaemia, postprandial glycaemia and LDLc, even when they lower compared to the current recommended values for the patients with DM. Lowering body fat in the patients with DM has to be approached in the period of their pre-obesity.
Keywords: diabetes mellitus; diabetic foot; syndrome; glycated hemoglobin; body mass index; prognosis.